1995
DOI: 10.1111/j.1532-5415.1995.tb06626.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Beginning Medical Students Toward Older Persons: A Five‐Campus Study

Abstract: Beginning medical students have already formed some unfavorable attitudes about older persons. Few independent predictors (either sociodemographic or students' previous experiences) of student attitudes could be identified that would help in the selection of students who had more favorable attitudes toward older persons. Hence, attempts to generate physicians with good attitudes must rely on curricular efforts during medical school and residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 19 publications
10
70
1
2
Order By: Relevance
“…One study that measured organizational support for compassionate care was also included [39]. Three studies measured compassion in educational institutions, either as indicators of educator instructional performance and quality, or as attributes in residents, fellows or medical/nursing students [40][41][42]. Table 2 summarizes the characteristics of the compassion and compassionate care assessment instruments as reported in the included articles.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…One study that measured organizational support for compassionate care was also included [39]. Three studies measured compassion in educational institutions, either as indicators of educator instructional performance and quality, or as attributes in residents, fellows or medical/nursing students [40][41][42]. Table 2 summarizes the characteristics of the compassion and compassionate care assessment instruments as reported in the included articles.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The study's findings, however, conflict with those of studies conducted among medical and dentistry students which reported that these students held negative attitudes towards the elderly. 2,8 It is unclear why pharmacy students have favorable attitudes towards the elderly. In our study, the early pharmacy practice experience course in geriatrics may have contributed to the positive attitudes of students towards the elderly given that previous studies found that exposing students to a course in geriatrics improved their attitudes towards the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The second section of the questionnaire consisted of questions adapted from the 14-item Geriatrics Attitudes Survey developed at the University of California, Los Angeles. 2 This survey is a validated instrument with high reliability, validity, and sensitivity, 28 designed to measure primary care residents' attitudes toward older people and geriatric patient care 2 and has been used in previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations